World Campaign of Youth Actions against the Nuclear Threat for Peace and Disarmament // Join the Fight // Peace is our Common Right
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Friedensbewegung politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung Sicherheitspolitik;Verteidigung;Bewaffnung